The Role of Knowledge Management in Managing Students' Creative Thinking Skills Using the Project Based Learning Model in the Era of Industrial Revolution 4.0 - Baiq Ertin Helmida,MP; Rosyia Wardani; Indah Arrifianti; Susilo Utomo (Dinasti Publisher, 2024)
This research aims to determine the effectiveness of implementing the Project Based Learning Model in improving creative thinking skills in Cirebon Regency High Schools and the differences between each school. The method used in this research is research and development or